2018
DOI: 10.3390/ani9010007
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance, Antioxidant Capacity, Lipid-Related Transcript Expression and the Economics of Broiler Chickens Fed Different Levels of Rutin

Abstract: Simple SummaryPoultry makes a substantial contribution to food security and nutrition. A growing human population and rising incomes have resulted in an increased demand for white meat. Poultry is the fastest growing animal production sector. Rutin, a natural growth and health promoter, was used at three levels for broiler feed (0.25, 0.5 or 1 g rutin/kg). Supplementing broiler diets with rutin, especially at 1 g/kg, has a variety of growth-promoting effects. It enhances antioxidant capacity and suppresses lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 53 publications
4
39
1
Order By: Relevance
“…In addition. Lutin supplementation reduced serum total cholesterol, triacylglycerol levels in Broiler Chickens [88].…”
Section: Discussionmentioning
confidence: 93%
“…In addition. Lutin supplementation reduced serum total cholesterol, triacylglycerol levels in Broiler Chickens [88].…”
Section: Discussionmentioning
confidence: 93%
“…In recent years many scientist showed interest in researches about oxidative stress and antioxidant agents. Among these antioxidant agents natural substances attracted most of the attention because these substances can prevent diseases and positively affect the health (Hassan et al, 2018). The efficacy of garlic preparations or extracts to alleviate free radical damage to biological membranes or other biological systems has been demonstrated (Horie et al, 1989;Knasmüller et al, 1989;Kourounakis & Rekka, 1991;Chung, 2006).…”
Section: The Effect Of Dietary Garlic (Allium Sativum) Black Cumin (mentioning
confidence: 99%
“…Use of active compounds of phytogenic origin has received extensive attention due to their wide spectrum of functions. Studies with polyphenols revealed that the addition of phenolic compounds improved the performance and feed efficiency ( Hassan et al, 2019 ). These polyphenols are mainly concentrated on the pericarp/outer protective layers of fruit or seed.…”
Section: Introductionmentioning
confidence: 99%